Evaluating Single‐ Versus Chase‐Boat Low‐Frequency Electrofishing for Assessing Flathead Catfish and Blue Catfish Populations in a Large River. (15th June 2022) - Pritt, Jeremy J.; Tyszko, Stephen M.; Conroy, Joseph D.; Zweifel, Richard D.
Abstract: Fisheries managers commonly use low‐frequency electrofishing to survey Flathead Catfish Pylodictis olivaris and Blue Catfish Ictalurus furcatus populations; however, inconsistent methods prohibit comparisons among studies. Here, we simultaneously sampled Flathead Catfish and Blue Catfish to compare single‐ and chase‐boat low‐frequency electrofishing configurations in five Ohio River navigational pools and inform standard sampling of these catfishes. Our objectives were to (1) compare Flathead Catfish and Blue Catfish CPUE among length categories, (2) evaluate the prevalence of high‐catch samples, and (3) determine the number of 15‐min electrofishing sites needed to achieve predefined precision and catch objectives between single‐ and chase‐boat configurations. The chase‐boat configuration produced greater catches of both Flathead Catfish (mean total CPUE was 44.6 fish/h for the chase‐boat configuration versus 32.8 fish/h for the single‐boat configuration) and Blue Catfish (mean total CPUE of 6.8 fish/h for the chase‐boat configuration versus 2.8 fish/h for the single‐boat configuration). Zero‐inflated negative binomial models revealed that CPUE was greater with the chase boat for both Flathead Catfish and Blue Catfish across substock, stock–quality, and quality and larger length categories. High‐CPUE samples (total CPUE >52 Flathead Catfish/h or >8 Blue Catfish/h) were more likely with the chase‐boat configuration than the single‐boat configuration. We found that a similar number of sites were needed to achieve the precision objective (relative standard error of CPUE <25%) for both configurations for Flathead Catfish; however, to achieve the precision objective for Blue Catfish, more single‐boat sites/pool were needed compared to chase‐boat sites/pool. To achieve the catch objective (capture 100 stock‐length catfish/pool), more single‐boat sites/pool were needed than chase‐boat sites/pool for both species. Our results suggest that using a chase boat better indexes the abundance of Flathead and Blue catfish, particularly when high catches are possible. However, more research is needed to inform the standardization of low‐frequency electrofishing for sampling catfishes in large river systems.